Comparison Lift and Drag of Airfoil NACA 1408 Standard and Modification Using Computational Fluid Dynamic - Usin Usin; Yolli Fernanda; Arwizet Karudin; Andre Kurniawan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
An airfoil is a geometry shape of an aircraft wing designed to produce high lift force and low drag forces. Study on the air flow and pressure around of the airfoil was important step to analysis lift force and drag force. Factor affecting the lift force and drag force airfoil are the geometry and dimensions of the airfoil. This study to discus about the modification airfoil NACA 1408 was performed by adding round tip in leading edge to obtain simulate air flow by varying the angle of attack. The result showed that coefficient of lift (Cl) and coefficient of drag (Cd) was calculated from the simulations, data the highest Cl and Cd were 0.00277 and 0.00025 for the standard airfoil and for modification airfoil were 0.00343 and 0.00064. Based on the test result, the modified airfoil can produce better lift force than the standard shapes for test speed of 20 m/s. Airfoil merupakan bentuk geometri sayap pesawat terbang yang dirancang untuk menghasilkan lift force tinggi dan drag force rendah. Studi tentang aliran udara dan tekanan di sekitar airfoil adalah langkah penting untuk menganalisis lift force dan drag force. Faktor yang mempengaruhi lift force dan drag force airfoil adalah geometri dan dimensi airfoil tersebut. Penelitian ini membahas tentang modifikasi dilakukan pada airfoil NACA 1408 dengan menambahkan ujung bulat pada leading edge dan mendapatkan simulasi aliran udara dengan memvariasikan angle of attack. Hasil penelitian menunjukkan bahwa coefficient of lift dan coefficient of drag dihitung dari simulasi, data coefficient of lift dan coefficient of drag tertinggi adalah 0.00277 dan 0.00025 untuk airfoil standar dan untuk airfoil modifikasi adalah 0.00343 dan 0.00064. Berdasarkan hasil pengujian, airfoil modifikasi dapat menghasilkan lift force lebih baik daripada bentuk standar untuk kecepatan uji 20 m/s.